Distance STEM Educators' Perceptions of Teachers’ Role - M.Said Dogru; Fatih Yüzbasioglu (Journal of Education in Science, Environment and Health)
STEM education has an important place in recent studies. With the Covid 19 pandemic, distance education applications have gained importance all over the world. STEM education applications have also turned into distance STEM education with the Covid-19 pandemic. The purpose of this study is to better understand STEM teachers' perceptions of online group education and how they perceive group education expectations. In this study, semi-structured interviews were conducted with secondary school STEM teachers. The interview was aimed at illuminating teachers’ perceptions of the role and purpose of teachers, and students’ expectations from a group science lesson. Themes arising from the thematic analysis of interviews were determined. The themes that emerged from the analysis are as follows: Teachers’ perceptions of their teaching role, teachers’ perceptions of students’ psycho-social needs, and teachers’ perceptions of students’ educational needs. Promoting student interaction in online synchronous education was identified as a challenge. Besides, some discrepancies were observed between teachers' perceptions of students learning expectations and their preferred approaches, and it was found that students expect a didactic experience rather than an interactive one.